2017
DOI: 10.1103/physreva.95.042329
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of loop state-preparation-and-measurement tomography

Abstract: We have performed an experiment demonstrating that loop state-preparation-and-measurement (SPAM) tomography [C. Jackson and S. J. van Enk, Phys. Rev. A 92, 042312 (2015)] is capable of detecting correlated errors between the preparation and the measurement of a quantum system. Specifically, we have prepared pure and mixed states of single qubits encoded in the polarization of heralded individual photons. By performing measurements using multiple state preparations and multiple measurement device settings we ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…We have shown that loop SPAM tomography is capable of detecting correlated errors between measurements performed on two spatially separated qubits. This, combined with the fact that previous experiments have demonstrated its ability to detected correlated errors between state preparations and measurements [4], further demonstrates the utility of loop SPAM tomography. Because it works in a device-independent manner, with a minimum of assumptions, loop SPAM tomography promises to be a useful and effective tool for detecting correlated errors in a wide variety of quantum information processing systems.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We have shown that loop SPAM tomography is capable of detecting correlated errors between measurements performed on two spatially separated qubits. This, combined with the fact that previous experiments have demonstrated its ability to detected correlated errors between state preparations and measurements [4], further demonstrates the utility of loop SPAM tomography. Because it works in a device-independent manner, with a minimum of assumptions, loop SPAM tomography promises to be a useful and effective tool for detecting correlated errors in a wide variety of quantum information processing systems.…”
Section: Discussionmentioning
confidence: 60%
“…It is called the partial determinant because it is mathematically similar to the determinant, but it is not a scalar quantity-it is a matrix of smaller size than E . It can be shown that the measured data are internally consistent as described above, and free of correlated SPAM errors, if and only if ( ) 1 E D = , where 1 is the 3x3 identity matrix [1][2][3][4]. No knowledge of the state ρ or the detector operators is necessary to make this determination.…”
Section: A Loop Spam Tomographymentioning
confidence: 88%
“…One can go one step further than self-consistent tomography and perform overcomplete sets of measurements on overcomplete sets of states that allow one to check the assumption that a given state-preparation procedure indeed produces a single specific state, and that a given measurement procedure indeed produces a single specific measurement. In particular, "holonomic" SPAM tomography or "loop" SPAM tomography denote a procedure to check for correlations between measurement and statepreparation [10,11]. For example, suppose one uses a laser to perform a measurement on a system whose state was prepared using that same laser just a microsecond ago.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various different forms of quantum tomography have been developed recently for experimentally determining individual POVM elements P k . Detector tomography [3][4][5][6][7][8][9], self-consistent tomography [10], and SPAM tomography [11][12][13] use different sorts of assumptions to estimate from experimental data what POVM element corresponds to a given outcome of a quantum measurement.…”
Section: Introductionmentioning
confidence: 99%
“…we find the normalized a posteriori probability distribution over ω that outcome k implies as å Analogously, we can define an a posteriori probability distribution over detection times of the photon as i (t) defined in(13). These probability distributions are over continuous quantities.…”
mentioning
confidence: 99%